'A city is not a company, a flat is not a commodity': urban movements and defenders of tenants' rights in Poland. (4th March 2018) - Żuk, Piotr
Abstract: This article describes urban and tenant movements that have been created in Poland in response to the commercialization of urban space and the complete commodification of the right to housing. On the one hand, spatial segregation in Polish cities was fully approved by the state; on the other hand, it became a source of income for new owners of acquired buildings, who often used criminal methods to intimidate tenants. Brutal evictions encountered social resistance from the emerging tenant movement, non-institutionalized left-wing communities and endangered tenants, who were often pensioners and members of the lower classes. The author mentions undertaken and possible methods of social self-defence such as eviction blockades and rent strikes. He also raises the question of whether urban movements can become part of a broader social movement for systemic change.